Investigating the effects of the heavy metals mercury, nickel and manganese, alone and in combination, on human erythrocytes and components of the coagulation system - Oberholzer, Hester Magdalena (University of Pretoria, 2024)
Dissertation (MSc (Anatomy))--University of Pretoria, 2019.